1998
DOI: 10.1590/s0100-879x1998000500007
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the intrinsic nervous system of the wild rodent Calomys callosus digestive tract. II: The submucous plexus

Abstract: The submucous plexus of the normal small and large intestine of Calomys callosus was studied by NADH and AChE histochemical techniques and by transmission and scanning electron microscopy.The plexus contains ( x _ ± SD) 7,488 ± 293 neurons/cm 2 in the duodenum, 5,611 ± 836 in the jejunum, 2,741 ± 360 in the ileum, 3,067 ± 179 in the cecum, and 3,817 ± 256 in the proximal colon. No ganglia or nerve cell bodies were seen in the esophagus, stomach, distal colon or rectum. The neurons are pear-shaped with a round … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The 2nd‐ and 3rd‐order bundles of fibres formed connections with the internal submucosal plexus (Balemba et al., ). Morphological and quantitative analysis of neurones in the submucosal plexus carried out in Calomys callosus (Souza et al., ) showed that the average number of ganglion neurones varied in different sections of the intestine – 293/cm 2 in the duodenum, 836/cm 2 in the jejune and 2741/cm 2 in the ileum – and the cells exhibited AChE positive activity, which was also confirmed by the observations in chinchillas.…”
Section: Discussionmentioning
confidence: 67%
“…The 2nd‐ and 3rd‐order bundles of fibres formed connections with the internal submucosal plexus (Balemba et al., ). Morphological and quantitative analysis of neurones in the submucosal plexus carried out in Calomys callosus (Souza et al., ) showed that the average number of ganglion neurones varied in different sections of the intestine – 293/cm 2 in the duodenum, 836/cm 2 in the jejune and 2741/cm 2 in the ileum – and the cells exhibited AChE positive activity, which was also confirmed by the observations in chinchillas.…”
Section: Discussionmentioning
confidence: 67%
“…Moreover, the adrenergic fibres came into contact with blood vessels and mucosal glands [6]. Striated muscles build the wall of the oesophagus in wild mouse (Calomys callosus) and hamster, and in these species only nerve fibres formed the submucosal plexus [17,22]. In cat, analysis of the density of ganglionic neurons in the submucosal plexus with mixed muscle type revealed the presence of only nerve fibres, and in opossum there was an increase in the number of neurons in the caudal direction [23].…”
Section: Discussionmentioning
confidence: 99%